A political biography of Coronacion Chiva. - Braselino, Vener P.; Viajar, Rodolfo U. (1998.)
The study reconstructs the personal and family life of Coronacion Chiva; identifies the factors and circumstances that led to her involvement in the Hangaway nga Manluluwas sang Banwa (HMB) and New People's Army (NPA) in Panay from the 1940's until the 1970's and analyzes the role she played in these revolutionary movements., This study employs a historical-descriptive approach and gives light to the rich and colorful life of Coronacion "Waling-waling" Chiva as a revolutionary and as a mother. The decision of Coronacion to join the HMB could be attributed to the socio-economic and political situation of the province before and right after the defeat of the Japanese forces. Rampant land grabbing and the injustices committed by the government on people pushed people like Coronacion to join organized revolutionary movements to, more effectively, clamor for change. The study greatly contributes to studies on women which deconstructs the traditional writing of history or men's history. It gives credit to Coronacion who played a vital role in the HMB as double for the Supremo and later, by mothering to the NPA. Aside from the invaluable help she has extended to the HMB and NPA by recruiting other women to the movement, she also served as an inspriation for her children, comrades and other people because of her courage. Her mere presence boosted the moral of her comrades. She was widowed a year after her marriage with, the USAFFE soldier, Jesus Lagura. While in the movement, she met Fernandito Tugonon. They were married in the movement and were blessed with five children. Her involvement to the NPA movement, even at an old age, led to her death. On August 16, 1977, while attempting to cross a river, Coronacion was killed by two unidentified men.
Research Paper (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Chiva, Coronacion